Visual Forms and Famininity Values of Wayang Golek Purwo Typical of Kuningan West Java - Hadijah, Ijah; Rohidi, Tjetjep Rohendi; Iswidayati, Sri (Universitas Negeri Semarang, 2018)
Visual signs as a symbol and philosophical value of femininity in wayang golek purwa at this time is less understood by some Pasundan people in Kuningan regency of West Java due to the strong influence of modernization. The problems in this research is how the visual form and femininity values ​​in wayang golek purwa typical of West Java Kuningan.This study aimed at explaining the visual form and the femininity values of wayang golek Purwa typical of West Java. This research utilized a descriptive method with socio-cultural approach based on post-positivism philosophy in the semiotics theory of Roland Barthes and Ferdinand De Saussure. The findings of this research is that the visual form of female characters in wayang golek purwa typical of West Java Kuningan is a denotative sign embodiment that retains the existing visual patterns of the puppet way puppet purwa. Meanwhile, the connotative values signifies that the existing wayang golek purwa typical of Kuningan West Java gives an illustration of the noble values ​​contained in the female characters of the puppet, that is the value of wisdom, holiness, manners, and feminism.